PEMILIHAN FONDASI CSTR UNTUK PRODUKSI BIOGAS DARI POME DALAM RANGKA MENINGKATKAN PENGEMBANGAN ENERGI TERBARUKAN - Herman Hidayat; Samdi Yarsono; Imaduddin Haq; Kornelis Kopong Ola; Agus Hadi Santosa Wargadipura; Winda Wulandari; Bambang Muharto (Badan Pengkajian dan Penerapan Teknologi, 2020)
Renewable energy development for power generation is in line with the government's program toincrease the share of renewable energy in the national energy mix which is relatively small at themoment. BPPT, collaborating with PTPN 5 in the Insinas Flagship program, built a pilot plant for biogasproduction from Palm Oil Mill Effluent (POME) with a capacity of 700 kW. The reactor used in this pilotproject is a Continuous Stirred Tank Reactor (CSTR) which is the most important operating unit forproducing biogas from POME. Therefore, the selection of the CSTR foundation is crucial since themain process occurs in the reactor. The scope of this activity is to realize the final design into theconstruction of a CSTR pilot plant. Several types of foundations were studied, starting from shallowfoundation type such as tread foundation, deep foundation, until combining shallow foundation typewith deep foundation type. The evaluation of existing data and design review indicates that the use ofMat Foundation is not suitable due to soil condition at a depth of 0–5m which is in the form of sandyloam soil with an NSPT value of less than 20. The selection of Piles is based on the calculations usingtotal vertical load of 3035,37 ton and total horizontal load of 542,57 tons. Considering the availability ofmaterials and time concern, the recommended foundation type is pile with a diameter of 600 mm typeB and a length of 12 m.